Analisis Faktor Yang Mempengaruhi Keputusan Siswa Memilih Lembaga Pendidikan - Ismu Kusumanto; Yusup Rianto (UIN Sultan Syarif Kasim Riau, 2012)
Learning institution be present at competition era between Learning institutions and then prosecute the Learning institutions to fulfill market need and want. This research used the variable, the price, the delivery system, and physical facilities, and communication. The methods of this research is cluster analysis. Based on the data analysis, it is obtained that for cluster I (53% respondent) have the characteristics that they are interested in following the programs given by this learning institution, the adjustment of the programs and the students’ major in SMA/K, and there should be special training in order to meet the demands of the working life, the price should be based on the quality of the training given to the students, and the facilities supporting the learning and teaching process are suitable to the students’ needs, the learning institution has complete facilities, and the brochure that gives all information of this learning institution are well designed so that it gives clear information about the learning institution, and the telecommunication media is by using email in order to deliver the information and daily assignment. In Cluster II (20% of the respondents) have the characteristics that the facilities are equals, and the price is reasonable, and this learning institution is categorized as moderate. In cluster III (27% of the respondents) have the characteristics of technology advance, interested in scholarship, there is written announcement, personal relationship, and has the website for the learning institution. Based on all of the three clusters, cluster I has the most respondents, that is 53%. Therefore, the strategy of the marketing can be focused on the cluster I.Key word: Cluster Analysis, Learning Institution, Marketing Strategy.